Kunst in België : Anno 1978. - Duchateau, Marcel; Van Tieghem, Jean-Pierre (Brussel : Nationale Kunstuitgaven A. de la Hamaide, 1978)
Algoet, Eric ; Annaert, Oscar ; Anthoons, Willy ; Antoine, Paul ; Baeyens, Marie-Thérèse ; Bal, Julien Englebert ; Beckers, Jaak Anton ; Beekman, Jan ; Bergen, Emiel ; Berbe, Guy ; Bilstein, Renee ; Bostoen, Lieva ; Bogart, Bram ; Bogaert, Andre ; Bogaert, Gaston ; Burssens, Jan ; Bury, Pol ; Caille, Pierre ; Camus, Gustave ; Borgrave, Elie ; Canestraro, Livia ; Carcan, Rene ; Cassiman, Jacques ; Capitan ; Cardon, Eric ; Chaidron, Jacques ; Chariot, Pierre ; Coenen, Jean-Claude ; Coulon, Berthe ; Courtois, Albin ; Cox, Jan ; De Bie, Eugene ; De Bruyne, Pieter ; De Blander, Anny ; De Clercq, Maurice ; Decock, Gilbert ; de Hemptinne, Chantal ; Delhaye, Claude ; Delhaye, Cecile ; Delogne, Jean ; De Kramer, Enk ; De Maeyer, Jacky ; Delvaux, Paul ; De Leeuw, Bert ; De Mey, Jos ; de Montpellier, Geoffroy ; Demeulemeester, Armand ; Denis, Philippe ; Deprez, Mia ; Depuydt, Stefaan ; De Roover, Carlo ; de Villeroux, Albert ; De Saedeleer, Jean-Pierre ; de Villegas de Clercamp, Brigitte ; de Villegas de Clercamp, Michael ; de Villers, Thierry ; De Vinck, Antoine ; De Vuyst, Gaspard ; De Vogelaere, Alfons ; D'Haese, Roel ; Dierickx, Karel ; Dionyse, Carmen ; Dooms, Vic ; Dries, Jan ; du Chastel, Simon ; Dudant, Roger ; Duchateau, Hugo ; Dupont, Veerle ; Edeline, Guillaume ; Elia, Elie ; Flausch, Fernand ; Frydman, Maurice ; Frimout, Cyr ; Feron-Baucher, Sylvie ; Foubert, Claude ; Gangolf, Serge ; Guebels, Monique ; Gentils, Vic ; Ghysebrechts, Louis ; Hoenraet, Luc ; Haardt, Gabrielle ; Haccuria, Maurice ; Holmens, Gerard ; Horvath, Pal ; Hoyos de Fernandez, Xavier ; Hoyos de Fernandez, Carmen ; Howet, Marie ; Huin, Rene ; Ickx, Nicole ; Ivens, Renaat ; Jans, Jos ; Javaux, Ginette ; Julien, Rene ; Jung, Simonetta ; Keelhoff, Alice ; Keil, Helene ; Kint, Magda ; Klein, Paul Georges ; Laffineur, Marc ; Lambrecht, Constant ; Leroy, Christian ; Landuyt, Octave ; Lenaerts, Fernand ; Leclercq, Guy ; Lyr, Claude ; Maieu, Frank ; Maeyer, Marcel ; Mara, Pol ; Minnaert, Frans
Minnebo, Hubert ; Moeschal, Jacques ; Monteyne, Roland ; Nellens, Roger ; Mandeville, Alfred ; Mulkers, Urbain ; Nicolai de Gorhez, Claudine ; Noel, Victor ; Nyns, Sophie ; Oosterlynck ; Pion, Jean-Louis ; Point, Jean-Pierre ; Poot, Rik ; Raveel, Roger ; Placeman ; Puissant, Ryta ; Rhaye, Yves ; Renson, Roland ; Riedel, Helene ; Ruyters, Simone ; Roelants, Karel ; Schelck, Maurice ; Slabbinck, Rik ; Sempels, Geo ; Somville, Roger ; Smeunincx, Willy ; Schmetz, Betty ; Souply, Emile ; Strebelle, Olivier ; Snoek, Paul ; Smet, Rene Louis ; Strebelle, Vincent ; Swimberghe, Gilbert ; Swingedau, Igor ; Wierusz-Kowalski, Tapta ; Szymkovicz, Charles ; Theys, Ivan ; 'T Kindt, Jacques ; Ubac, Raoul ; Urbin Choffray, Francine ; Uyttersprot, Jacqueline ; Vaes, Jef ; Vaes, Francis ; Van Aerden, Willem ; Van Aken, Teresa ; Van Breedam, Camiel ; Van Damme, Suzanne ; Van Bulck, Roger ; Vandekerckhove, Rita ; Van den Abbeel, Jan ; Van den Abeele, Remy ; Van den Brande, Frans ; Vandenbranden, Guy ; Van den Driessche, Lucien ; Van den Meersch, Vincent ; Van de Velde, Manu ; Van der Loo, Jan ; Van Gysegem, Paul ; Van Gindertael, Thomas ; Van Hecke, Herman ; Van Ruyssevelt, Jozef ; Van Sumere, Hilde ; Van Saene, Maurits ; Van Tuerenhout, Jef ; Van Landuyt, Jozef ; Vanvinckenroy, Monique ; Van Vlasselaer, Julien ; Veranneman, Emiel ; Van Wel, Jean ; Verduyn, Jacques ; Verjans, Raf ; Wallaert, Martin ; Vermeersch, Jose ; Winance, Alain ; Winance, Jran ; Willequet, Andre ; Wittevrongel, Roger ; Wolfs, Roger
boek